Early results of PRO-EPI: PROspective multicenter observational study on elective pelvic nodes irradiation in patients with intermediate/high/very high-risk non-metastatic prostate cancer submitted to radical, adjuvant, or salvage radiotherapy with or without concomitant androgen deprivation therapy - Guerini, Andrea Emanuele; Noale, Marianna; Mortellaro, Gianluca; Lisi, Roberto; Bruni, Alessio; Santini, Roberto; Muto, Paolo; Ferrera, Giuseppe; Cossali, Gianluca; Morelli, Vittorio; , PRO-EPI study group; Magrini, Stefano Maria; et al. (Frontiers in Oncology, 2022)
Forty-three Italian Radiation Oncology centers participated in the PROspective multicenter observational study on Elective Pelvic nodes Irradiation (PRO-EPI) project, with 1029 patients enrolled. In this preliminary analysis we longitudinally evaluated the impact of Elective Nodal Irradiation (ENI) and radiotherapy features on toxicity and quality of life (QoL). Six months follow-up data were available for 913 patients and 12 months data for 762 patients. Elective Nodal Irradiation was given to 506 patients (48.9%). Volumetric Intensity-Modulated Radiation Therapy (IMRT) was adopted in more than 77% of patients and Image-Guided Radiation Therapy (IGRT) in 84.4%. Androgen deprivation therapy (ADT) was administered to the majority of patients (68.3%) and it was associated to ENI in 408 cases (81.1%). Toxicity was mostly mild and reversible and IGRT resulted in a significant reduction of rectal toxicity, although a non-significant trend towards increased urinary toxicity was observed. No statistically significant differences in QoL and toxicity were seen in patients treated with or without ENI. The adoption of IGRT is widespread and increasing and could reduce treatment toxicity. ENI is not yet the standard treatment, but it is performed in a growing fraction of cases and not resulting into an increase in toxicity or in a deterioration of QoL. Further analyzes are needed to clarify the long-term toxicity profile and the impact of ENI on survival.